Silicon–aluminum synergistic mechanism in flame retardancy of epoxy resin. Issue 8 (18th December 2013) - Wang, Jiangbo; Li, Yongyou; Huang, Mengjiao; Fang, Jialin; Wang, Chengwei
<x xml:space="preserve">Abstract</x> In this article, the Kissinger method and the Flynn‐Wall‐Ozawa method were used to calculate the activation energy of thermal degradation process. Similar results were found in above two methods that the flame retardants polyepoxyphenylsilsesquioxane (PEPSQ) and aluminum hydroxide (ATH) improved the activation energy of epoxy resin (EP). The Flynn‐Wall‐Ozawa method further revealed that the addition of PEPSQ and ATH played an important role in improving the heat resistance and thermal stability of the system and produced synergistic effect in flame retardancy of EP through the significantly increment of the activation energy, especially in the final stage of the EP thermal degradation process. POLYM. COMPOS., 35:1553–1558, 2014. © 2013 Society of Plastics Engineers